Pembentukan Karakter Percaya Diri Melalui Pelatihan Public Speaking pada Siswa SMP di Kawasan Pesisir Teluk Tomini - Nuramila Nuramila; Munkizul Umam Kau (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Self-confidence is a character that must be instilled in oneself from an early age, especially in this case for teenagers in the coastal area of Tomini Bay. The coastal area of Tomini Bay has rich natural resource potential and diverse cultural diversity. However, this area often faces various challenges, especially in terms of education and character development of its young generation. Teenagers tend to feel unable to be equal to other teenagers in urban environments. This is because of their low self-confidence. Therefore, starting from this problem, the community service offers a solution by forming a self-confidence character through Public Speaking training for junior high school students in the coastal area of Tomini Bay. Public Speaking training gives students the opportunity to practice speaking in front of many people, be able to respond to feedback constructively, and overcome nervousness or anxiety. A structured and ongoing training program is expected to form a self-confidence character in students. The implementation of this community service activity uses a training method. This community service activity will be carried out at SMP Negeri 3 Satap Bonepantai. This school is one of the schools included in the coastal area of Tomini Bay. It is hoped that with this service, it can be a solution for the low level of student confidence to appear speaking in public in this case through Public Speaking training.